Guidelines for HTRF technology in EGFR kinase assay. Issue 4 (17th August 2022) - Liang, Yuan; Zhang, Tiehua
Abstract: Epidermal growth factor receptor (EGFR) is among the first discovered transmembrane receptor tyrosine kinases. Ligand binding to the extracellular domain of EGFR results in the formation of homo‐dimeric or hetero‐dimeric complexes, activation, and auto‐phosphorylation in the intracellular tyrosine kinase domain, then regulates the cell's proliferation, differentiation, migration, and invasion. It has been reported that EGFR is overexpressed, amplified, or mutated in several epithelial tumors. EGFR tyrosine kinase inhibitors (EGFR‐TKIs) specifically bind to the tyrosine kinase domain of EGFR. Homogeneous time‐resolved fluorescence (HTRF) assay is successfully used in kinase assays and is a crucial tool in the drug discovery of various kinases. Moreover, the HTRF assay has been determined to exhibit many advantages, such as being easy to miniaturize, simple to read, and excellent to repeat. In these guidelines, the theory, materials, and reagent preparation of HTRF kinase assay are described and emphasized. Furthermore, the protocol and optimization of the assay are determined to establish an HTRF screening platform, then an optimized HTRF kinase assay is performed to test the compounds for screening potential EGFR‐TKIs. In addition, these guidelines can contribute to verifying the high‐throughput screening results of HTRF and help to reveal the underlying mechanism of the EGFR kinase and tested compounds. Abstract : This study aims to provide the guidelines for homogeneous time‐resolved fluorescence (HTRF) assay for screening the potential epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors. HTRF is a simple, fast, and efficient method for drug screening in vitro.